IDENTIFIKASI FAKTOR PENYEBAB ANAK KELUARGA SEJAHTERA TIDAK MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI - Fadli M, Achsin; Zakso, Amrazi; Riva'i, Wanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe title of this research is ?The Identification of Causes Factors of Children From The Prosperous Family Who Not Continuing Their Education to The College (Case Study In Pasar Barito Sanggau)?. Common problem in this research is ?Why children from prosperous families there are not continuing their education to the college